2021
DOI: 10.1002/1873-3468.14055
|View full text |Cite
|
Sign up to set email alerts
|

Structural analyses of PCNA from the fungal pathogen Candida albicans identify three regions with species‐specific conformations

Abstract: An assembly of multiprotein complexes achieves chromosomal DNA replication at the replication fork. In eukaryotes, proliferating cell nuclear antigen (PCNA) plays a vital role in the assembly of multiprotein complexes at the replication fork and is essential for cell viability. PCNA from several organisms, including Saccharomyces cerevisiae, has been structurally characterised. However, the structural analyses of PCNA from fungal pathogens are limited. Recently, we have reported that PCNA from the opportunisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 89 publications
(135 reference statements)
0
18
1
Order By: Relevance
“…Although CaPCNA possesses significant IDCL sequence identity and belongs to group-I, contrary to the earlier report, CaPCNA is functionally noncompatible in S. cerevisiae (6,9,11). Our comparative structural analyses revealed that CaPCNA displayed noticeable structural alterations in the hydrophobic pocket, J loop, and P loop regions (9).…”
Section: Introductioncontrasting
confidence: 61%
See 4 more Smart Citations
“…Although CaPCNA possesses significant IDCL sequence identity and belongs to group-I, contrary to the earlier report, CaPCNA is functionally noncompatible in S. cerevisiae (6,9,11). Our comparative structural analyses revealed that CaPCNA displayed noticeable structural alterations in the hydrophobic pocket, J loop, and P loop regions (9).…”
Section: Introductioncontrasting
confidence: 61%
“…Despite our repeated efforts with varying concentrations of ScPCNA and T2AA, no significant heat exchange was observed, suggesting a weak or undetectable interaction between ScPCNA and T2AA. In our earlier study, we had observed that while human PCNA interacts quite strongly with T2AA, CaPCNA failed to show such binding, suggesting that T2AA has a higher affinity for group-II PCNA than for group-I PCNA (9). Although T2AA binds to NcPCNA, it does not inhibit NcPCNA functions in yeast cells, probably due to its lower affinity (M) than the human PCNA (nM) (Fig.…”
Section: Differential Interaction Of Scpol32 and T2aa With Scpcna And Ncpcnamentioning
confidence: 86%
See 3 more Smart Citations